Metal doping in topological insulators- a key for tunable generation of terahertz. (October 2020) - Sharma, Prince; Sharma, M.M.; Kumar, Mahesh; Awana, V.P.S.
Abstract: The unique surface edge states make topological insulators a primary focus among different applications. In this article, we synthesized a large single crystal of Niobium (Nb)-doped Bi2 Se3 topological insulator (TI) with a formula Nb0·25 Bi2 Se3 . The single crystal has characterized by using various techniques such as Powder X-ray Diffractometer (PXRD), DC magnetization measurements, Raman, and Ultrafast transient absorption spectroscopy (TRUS). There are (00l) reflections in the PXRD, and Superconductivity ingrown crystal is evident from clearly visible diamagnetic transition at 2.5 K in both FC and ZFC measurements. The Raman spectroscopy is used to find the different vibrational modes in the sample. Further, the sample is excited by a pump of 1.90 eV, and a kinetic decay profile at 1.38 eV is considered for terahertz analysis. The differential decay profile has different vibrations, and these oscillations have analyzed in terms of terahertz. This article not only provides evidence of terahertz generation in Nb-doped sample along with undoped sample but also show that the dopant atom changes the dynamics of charge carriers and thereby the shift in the Terahertz frequency response. In conclusion, a suitable dopant can be used as a processor for the tunability of terahertz frequency in TI. Highlights: Stretching of the quintuple layer of Bi2Se3. Raman Redshift in the Nb doped Bi2Se3. Superconductivity at 2.5K in Nb doped Bi2Se3. 1.99 THz generation by Nb doped Bi2Se3. Tuning of THz generation by metal doping.